Chromatin organisation in duckweed interphase nuclei in relation to the nuclear DNA content. (22nd May 2014) - Cao, H. X.; Vu, G. T. H.; Wang, W.; Messing, J.; Schubert, I.
Abstract: The accessibility of DNA during fundamental processes, such as transcription, replication and DNA repair, is tightly modulated through a dynamic chromatin structure. Differences in large‐scale chromatin structure at the microscopic level can be observed as euchromatic and heterochromatic domains in interphase nuclei. Here, key epigenetic marks, including histone H3 methylation and 5‐methylcytosine (5‐mC) as a DNA modification, were studied cytologically to describe the chromatin organisation of representative species of the five duckweed genera in the context of their nuclear DNA content, which ranged from 158 to 1881 Mbp. All studied duckweeds, including Spirodela polyrhiza with a genome size and repeat proportion similar to that of Arabidopsis thaliana, showed dispersed distribution of heterochromatin signatures (5mC, H3K9me2 and H3K27me1). This immunolabelling pattern resembles that of early developmental stages of Arabidopsis nuclei, with less pronounced heterochromatin chromocenters and heterochromatic marks weakly dispersed throughout the nucleus.